Digitalization Roadmap of the Russian Forestry and the Risks of Its Implementation - G. Sinyavsky, Nikolai; I. Alekseeva, Gulnara; A. Artamonova, Kira; N. Prizhennikova, Alyona; V. Stepashkin, Sergey; V. Kharchenko, Svetlana (International Journal of Psychosocial Rehabilitation, 2020)
Currently, digital technologies develop exponentially. Support for this process is provided at the state level in many countries. Russia has adopted program documents for the digitization of the country and the development of the forestry, which should be observed from a unified systemic position, taking into account not only the interests of the state but also the ones of business. We tried to consider the problems of the development of only one Russian industrial sector, the forestry, and how digitalization can help to solve these problems. We also tried to make an analysis of the risks arising in the industry on the way of its transformation. It is revealed that the Russian economy, in general, has the potential for digital transformations. There is also the desire to achieve results. However, the source of risks for forestry lies in the lagging behind the world level of the main Russian technologies used in forestry.